Displaced proximal humerus fractures treated with ORIF via the deltoid interfascicular approach vs the deltopectoral approach: A prospective case-control study. Issue 23 (10th June 2022) - Liu, Bin; Wang, Xinguang; Wang, Chao; Jiao, Zhenqing; Chen, Wei
Abstract: Background: The purpose of this study was to evaluate the clinical outcomes and complications of displaced proximal humeral fractures treated with proximal humeral internal locking system (PHILOS) plate fixation via a deltoid interfascicular (DI) vs a deltopectoral (DP) approach. Methods: This prospective case-control study was conducted with patients admitted to our hospital from May 2015 to June 2018 who suffered from unilateral displaced proximal humerus fractures. Patients were treated with PHILOS plate fixation via a DI (DI group) or DP approach (DP group). The clinical outcomes and complication data were collected for comparison between the 2 groups. The patients were followed up at 3, 6, and 12 months; and every 6 months thereafter. The patients' functional recoveries were evaluated according to the normalized Constant-Murley score, range of motion of the shoulder (flexion, abduction, external/internal rotation) and disabilities of the arm, shoulder and hand score. Results: A total of 77 patients, followed for an average of 15 ± 2.2months (range, 12–21), were enrolled (36 in DI group and 41 in DP group) for final analysis. No significant differences in age, sex, affected side, fracture type, injury mechanism or time from injury to operation were found between the 2 groups (all P  > .05). The incision length, intra-operative blood loss, and duration of operation in the DI group were significantly less than those in the DP group, respectively (all P  < .05). The functional outcomes assessed by the normalized Constant-Murley score and range of motion of flexion and internal rotation in the DI group were superior to those in the DP group at 3 and 6months after the operation ( P  < .05); however, no significant differences were observed at the 12-month and subsequent follow-ups (all P  > .05). There was no significant difference in the range of shoulder external rotation and abduction during the postoperative follow-ups ( P  > .05). At the last follow-up, the mean disabilities of the arm, shoulder, and hand score was 14.0 (6.6) points in the DI group and 14.4 (6.9) points in the DP group ( P  = .793). Complications occurred in 1 patient in the DI group and 8 patients in the DP group ( P  = .049). Conclusion: The current study demonstrates that DI approach is a safe and effective alternative for the treatment displaced proximal humerus fractures. The DI approach rather than DP approach was recommended when lateral and posterior exposure of the proximal humerus is required, especially when fixed with PHILOS plate.